The challenges of managing type 1 diabetes with other autoimmune diseases. (10th October 2022) - Salloum, Mohammed; Poole, Ruth
Abstract: People with type 1 diabetes have an increased risk of developing other autoimmune diseases compared to the background population and this risk has been increasing over the last 20 years. Coeliac disease affects absorption of food which can lead to hypoglycaemia in people with diabetes. Both conditions have dietary restrictions and managing the two can make food choices more difficult. Addison's disease can lead to significant challenges in managing blood glucose particularly in times of intercurrent illness and significantly increases morbidity and mortality in patients with diabetes. Thyroid disease, both hyperthyroidism (Graves' disease) and hypothyroidism (Hashimoto's thyroiditis) can affect blood glucose levels directly by changes in glucose uptake and metabolism or indirectly through changes in weight. Management of type 1 diabetes includes being alert to the possibility of these potential additional diagnoses. Copyright © 2022 John Wiley & Sons.